Analisis Rasio Likuiditas Dalam Mengukur Kinerja Keuangan PT Adira Dinamika Multi Finance Tbk Tahun 2020 - 2021 - Karunia Syiffani; Nurul Fatimah; Falecia Janeta (Shafin: Sharia Finance and Accounting Journal, 2022)
In this study, data were collected using 3 methods, namely by literature review, non-observational behavior in the form of an annual report published by Adira Dinamika Multi Finance Tbk for the period 2020 and 2021, and drawing conclusions. This study aims to determine and identify the liquidity ratios that have an influence on Adira Dinamika Multi Finance's ability to fulfill financial obligations to external parties. Based on the calculation results, it can be concluded that in 2021 the current ratio (Current Ratio), cash ratio (Cash Ratio), and cash exchange ratio (Turn Cash Ratio) have increased compared to 2020. The current ratio increased by 2.27%, the ratio cash increased by 0.12%, and cash exchange ratio increased by 1.15%.